2018
DOI: 10.1177/2055217318783347
|View full text |Cite
|
Sign up to set email alerts
|

Onset of secondary progressive multiple sclerosis is not influenced by current relapsing multiple sclerosis therapies

Abstract: BackgroundDisease-modifying therapies are thought to reduce the conversion rate to secondary progressive multiple sclerosis.ObjectiveTo explore the rate, chronology, and contributing factors of conversion to the progressive phase in treated relapsing–remitting multiple sclerosis patients.MethodsOur study included 204 patients treated for relapsing–remitting multiple sclerosis between 1995 and 2002, prospectively followed to date. Kaplan–Meier analysis was applied to estimate the time until secondary progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
2
26
0
2
Order By: Relevance
“…]” This concept implies the hypothesis that two different clinical forms of MS could coexist from the beginning of the disease: one with a relapsing debut, in which progressive MS will never develop, and the other with a relapsing course, but with a silent progression from the beginning, responsible for the subsequent progressive course of SPMS. Similar data were published by our group in a cohort of 204 RRMS patients followed for 20 years, work in which we discussed the concept of bout onset progressive MS (BOPMS), first mentioned by Paz Soldán et al…”
supporting
confidence: 82%
“…]” This concept implies the hypothesis that two different clinical forms of MS could coexist from the beginning of the disease: one with a relapsing debut, in which progressive MS will never develop, and the other with a relapsing course, but with a silent progression from the beginning, responsible for the subsequent progressive course of SPMS. Similar data were published by our group in a cohort of 204 RRMS patients followed for 20 years, work in which we discussed the concept of bout onset progressive MS (BOPMS), first mentioned by Paz Soldán et al…”
supporting
confidence: 82%
“…Research into how this transition can be prevented is therefore of vital importance. Disease course is often unpredictable, and the underlying mechanisms behind why some RR MS patients progress to SP MS and others do not is incompletely understood133 . The effect of MS DMD's once the progressive phase has been reached is less clear than is the case for RR MS, highlighting the importance of preventing transition to SP MS since treatments cannot necessarily be depended on to alleviate symptoms to the same degree134 .…”
mentioning
confidence: 99%
“…Naturally, certain risk factors have been described, which could suggest or predict the manifestation of secondary progression in MS patients. Among the demographic characteristics of the patients at the RRMS diagnosis, male sex ( 29 , 33 35 ), older age ( 21 , 29 , 35 38 ), and a multifocal disease manifestation at onset ( 36 , 37 ) have been associated with an earlier transition to SPMS. Regarding the disease course, patients with a low EDSS at MS diagnosis could have a lower risk of disability progression further on ( 36 ); the annual relapse rate may be a predictive factor especially in the earlier disease stages ( 27 , 29 , 35 , 36 ).…”
Section: Pathophysiology Of Disease Progressionmentioning
confidence: 99%
“…The use of DMTs seems to modify the risk of a secondary progressive course. First-line DMTs may prolong the period to transition to SPMS according to several studies ( 18 , 19 , 29 , 36 ), although a lack of an objective influence has also been suggested ( 37 , 41 ). Furthermore, the use of newer high-effective DMTs is associated with an even lower risk of disability accumulation compared to the first-line therapies ( 19 ).…”
Section: Pathophysiology Of Disease Progressionmentioning
confidence: 99%